ESTABLISHMENT OF LOMBOK STRAIT TRAFFIC SEPARATION SCHEME AND ITS IMPACTS ON MARITIME SECURITY - Syaiful Anwar (The Republic of Indonesia Defense University, 2021)
The Lombok Strait, which is part of the Indonesian Archipelagic Sea Lane II, has been established as a Traffic Separation Scheme, based on several considerations such as safety of navigation and preservation of the natural environment. This study aimed to explore the process of establishing the Lombok Strait Traffic Separation Scheme and to analyze its impacts on Indonesia's maritime security in the area. It was a qualitative study, using a case study approach. The data obtained from the literature study came from several scientific articles and government documents, interviews with several informants, and direct observations of the object under study. This study found that there were direct impacts of the establishment on the government institutions related to the management and execution of the Traffic Separation Scheme, on the adequacy of infrastructure related to the supervision and control of the Traffic Separation Scheme, and in the long term, there will be various potential impacts in form of several threats to Indonesia's maritime security, such as piracy, armed robbery, sea accidents, smuggling, pollution, and terrorism.